Application of the Demonstration Method in Improving Student’s Abilities in Describing Physical Appearance and Personality - Zetira Ahmad; Muhammad Irfan Almu'afi (Indonesian Journal of Multidisciplinary Scientific Studies, 2024)
The ability to describe people is one of the important skills in learning English. This skill allows students to be able to understand and describe a person's personality and physical appearance appropriately. In learning English, it is important to improve students' communication skills in English and prepare them to interact with foreigners or in an international environment. This study aims to improve the results of learning English in class V SD Negeri 057214 Muka Paya. In the pre-cycle, 50% of students had not reached the KKM. After the improvement in cycle I with the demonstration method, the percentage of students who had not completed it decreased to 35%. In cycle II, by repeating the previous material and interactive activities, it managed to achieve a success indicator of 90%. There was an increase in teacher skills and student participation. Factors causing low learning outcomes include lack of interaction, focus on delivering material, and absence of questions. The results of this study indicate success in improving student learning outcomes in describing people's physical appearance and personality.